To Evaluate the Endometrial Histopathological Etiology of Abnormal Uterine Bleeding: A Hospital Based Observational Study - Namrata Sharma; Pallavi Sharma (Asian Journal of Medical Research, 2019)
Background: The study of endometrial microscopy in women with AUB is helpful to distinguish anovulatory from ovulatory AUB and to diagnose hyperplasia and carcinoma of endometrium. The aim of this study to find out the endometrial histopathological causes of abnormal uterine bleeding. Subjects and Methods: A hospital based descriptive type of observational study done on all abnormal uterine bleeding cases of age above menarche attending the outdoor of Government hospital & Government Medical College, Bharatpur (raj.). The study material consisted of endometrial curettings from 100 patients attending Gynecology OPD. These patients were having a clinical diagnosis of Abnormal uterine bleeding. Endometrial curettage samples were fixed in 10% formalin and histopathological slides were prepared sand Hematoxyline and Eosin staining was done. Results: In the present Study, high incidence of AUB was noted in 31-40 years (42%). The incidence of AUB in the reproductive age group was 57%. Conclusion: We concluded that dilatation and curettage is useful for diagnosis, to assess therapeutic response and to know the pathological incidence of organic lesions in cases of abnormal uterine bleeding prior to surgery.